Teachers’ views on the innovative techniques needed for effective teaching and learning in post primary schools in Nigeria - Eze, P.I. (Journal of Education, Health and Sport, 2017)
This study was carried to investigate teachers’ views on the innovative techniques needed for effective teaching and learning in Nigeria post primary schools. Four research questions were formulated to guide the study. Simple random sampling technique was used to obtain 150 respondents for the study from 15 public secondary schools in Ebonyi Local Government Area of Ebonyi State, Nigeria. An internal consistency reliability estimate of 0.78 was established. Instrument used to collect data was structured questionnaire. Data collected were analyzed using mean and standard deviation. It was found among others that the individualized instructional technique, language laboratory technique, and PowerPoint technique enhanced teaching and learning in post primary schools. The educational implication of the results include that effective teaching and learning is influenced by individualized institutional technique, language laboratory technique, and PowerPoint technique. Conclusions have been drawn and recommendations are made.